Feasibility Analysis Of Free Space Earth To Satellite Optical Link In Tropical Region - M. Nor, Norhanis Aida; Islam, Md. Rafiqul; Al-Khateeb, Wajdi (IIUM Engineering Journal, 2012)
Free Space Optics (FSO) becomes a great attention because of the chances in transmitting data up to 2.5Gbps. There are a lot of advantages offered by FSO such as easily deployment with saving time and cost and no electromagnetic interference. In spite of the advantages, FSO has an uncontrolled drawback which is highly sensitive to atmospheric phenomena because uses air as tranmission medium. Current studies and researches are only focusing on FSO terrestrial link with short path length and based on data from temperate region. Therefore, this paper is aiming to provide feasibility analysis of FSO link from earth to satellite especially Low Earth Orbit (LEO) based on atmospheric data in tropical region. The analysis will include the losses from geometrical attenuation, absorption, scintillation, haze attenuation, and rain attenuation. ABSTRAK: Ruang Bebas Optik (Free Space Optics (FSO)) mendapat perhatian kerana kebolehannya memancarkan data pada kelajuan tinggi. Di sebalik kelebihannya, FSO amat sensitif terhadap fenomena atmosfera kerana ia menggunakan udara sebagai perantara transmisi. Penyelidikan dan kajian terkini hanya memfokus kepada jalinan darat FSO dengan kepanjangan jarak pendek dan bergantung kepada kawasan tenang. Oleh itu, kertas ini menyasarkan untuk memberikan analisis kebolehlaksanaan jalinan FSO dari bumi ke satelit terutamanya Orbit Rendah Bumi (Low Earth Orbit (LEO)) bergantung kepada data atmosfera di kawasan tropika. Analisa termasuklah kehilangannya akibat pengecilan geometri, penyerapan, kelipan, pelemahan jerebu dan pelemahan hujan. KEYWORDS: feasibility; Free Space Optics; availability; atmospheric attenuation; beam divergence angle; elevation angle